Sacred architecture + design : churches, synagogues, mosques, temples - Uffelen, Chris van (Salenstein : Braun, 2014)
" Sacred buildings are among the oldest types of edifice produced in human civilisation. As they have throughout history, the construction of churches, synagogues, mosques and other building which are used for sacred, ritual or ceremonial acts is still considered the most prestigious of construction tasks. Next to functional demands, which are heavily ritualized in liturgical practice, the architects must concentrate particularly on the aesthetic expression. The space must operate as a framework for belief, with specific reference to the religion to be served. It must also be an appropriate stage for the experience of the divine service and concomitant spirituality. This volume shows exceptional examples of buildings from the various religions and denominations which often attain the status of works of art. By acknowledging the concept of world religions, exciting parallels and clear distinctions in contemporary sacred architecture emerge.
Includes index
Keywords: Religious architecture; Religious facilities; Sacred space